A Rape in the Early Republic : Gender and Legal Culture in an 1806 Virginia Trial - Smyth, Alexander, 1765-1830 (Book collections on Project MUSE., 2017)
On January 14, 1806, Sidney Hanson was raped by John Deskins on a rough gravel path in the woods in Tazewell County, Virginia. In the early nineteenth century, trials for rape were rare. Scanty court records typically lacked the detail needed to reconstruct the lives of those involved and evaluate the social and physical setting of the crime. Yet the events on that fateful day in 1806 would be the exception. In A Rape in the Early Republic, Randal L. Hall reproduces the complete trial testimony of Alexander Smyth, the prosecutor for Hanson's trial. Smyth's detailed record offers a revealing glimpse into how early rape cases moved through the legal system, first at the local level and then in the state's recently created district court system. It also shows that Deskins was not the only one on trial -- Hanson's character was being scrutinized as well. Hall's introduction, rather than offering an analysis of Smyth's documents, provides important context and highlights historical themes that Hanson's situation illustrates. Featuring classroom discussion ideas and a list of suggested reading, A Rape in the Early Republic will be a valuable resource for students and scholars as well as anyone interested in gender, law, and society in the early republic.